THEOLOGY OR "CHRISTIAN IDEOLOGY" – THE PROBLEM OF HUBRIS - Pillay, G. J. (Scriptura, 1985)
In addressing the question: is the church in South Africa truly the Church of Christ, and its message truly Gospel?, the author contends that Christianity in South Africa is to a large extent system-bound, and therefore idolatrous. Because theology is a continuous critical quest, and its task not only to clarify and confirm or evaluate, but also to re-examine the church’s teaching, believers should commit themselves to a critical analysis of the fundamental issues of the present system. An ideological breakthrough is needed to change society’s consciousness and could be brought about if the churches, as communities of faith, were to present the Gospel to deliver man from dehumanisation within his own systems. When the church is truly Church, the questions that have hitherto caused anxiety, would find their own resolution.